Broad-spectrum treatment of bacterial biofilms using magneto-responsive liquid metal particles. Issue 47 (6th November 2020) - Cheeseman, Samuel; Elbourne, Aaron; Kariuki, Rashad; Ramarao, Aswin V.; Zavabeti, Ali; Syed, Nitu; Christofferson, Andrew J.; Kwon, Ki Yoon; Jung, Woojin; Dickey, Michael D.; Kalantar-Zadeh, Kourosh; McConville, Christopher F.; et al.
Abstract : Broad-spectrum treatment of monoculture and mixed species biofilms using magnetically actuated, liquid metal particles. Abstract : The formation and proliferation of bacterial biofilms on surfaces, particularly those on biomedical devices, is a significant issue that results in substantial economic losses, presenting severe health risks to patients. Furthermore, heterogeneous biofilms consisting of different bacterial species can induce the increase in pathogenicity, and the resistance to antimicrobial agents due to the synergistic interactions between the different species. Heterogeneous bacterial biofilms are notoriously difficult to treat due to the presence of extracellular polymeric substances (EPS) and, in conjunction with the rapid rise of multi-drug resistant pathogens, this means that new solutions for anti-biofilm treatment are required. In this study, we investigate the application of magneto-responsive gallium-based liquid metal (GLM-Fe) nanomaterials against a broad range of Gram-positive and Gram-negative bacterial mono-species and multi-species biofilms. The GLM-Fe particles exhibit a magneto-responsive characteristic, causing spherical particles to undergo a shape transformation to high-aspect-ratio nanoparticles with sharp asperities in the presence of a rotating magnetic field. These shape-transformed particles are capable of physically removing bacterial biofilms and rupturing individual cells. Following treatment, both mono-species and multi-species biofilms demonstrated significant reductions in their biomass and overall cell viability, demonstrating the broad-spectrum application of this antibacterial technology. Furthermore, the loss of integrity of the bacterial cell wall and membranes was visualized using a range of microscopy techniques, and the leakage of intracellular components (such as nucleic acids and protein) was observed. Insights gained from this study will impact the design of future liquid metal-based biofilm treatments, particularly those that rely on magneto-responsive properties.